Comparison of pre-competitve anxiety between fight and handball athletes (Research, Society and Development, 2020)
Objective: The aim of this study was to compare pre-competitive anxiety athletes in wrestling and handball, and to verify the relationship of pre-competitive anxiety with age. Methods: Participated in this cross-sectional study 62 athletes (32 Chinese boxing and jiu-jtsu and 20 handball), both genders (55 men and 7 women), with a mean age of 24.25 ± 4.71 years. The instrument used was the reduced version of Competitive State Anxiety Inventory-2 (CSAI-2R). Data analysis was conducted using Generalized Estimation Equations (EGG) and Pearson correlation (p